Aldosterone and renin in cardiac patients referred for catheterization. Issue 25 (June 2017) - Erne, Paul; Müller, Andrea; Rossi, Gian Paolo; Seifert, Burkhardt; Stehlin, Fabrice; Redondo, Maurice; Bauer, Peter T.; Kobza, Richard; Resink, Therese J.; Radovanovic, Dragana
Abstract : Abstract: Little is known regarding alterations of the renin-angiotensin system in patients referred for cardiac catheterization. Here, we measured plasma levels of active renin and aldosterone in patients referred for cardiac catheterization in order to determine the prevalence of elevated renin, aldosterone, and the aldosterone-renin ratio. A chemiluminescence assay was used to measure plasma aldosterone concentration (PAC) and active renin levels in 833 consecutive patients, after an overnight fasting and without any medication for least 12 hours. We evaluated associations of the hormonal elevations in relation to hypertension, atrial fibrillation (AF), hypertensive cardiomyopathy, coronary artery disease (CAD), valvular disease, impaired left ventricular ejection fraction (LVEF < 35%), and pulmonary hypertension (arterial pulmonary mean pressure >25 mm Hg). Hyperaldosteronism occurred in around one-third of all examined patients, without significant differences between patients with or without the named cardiac diseases. In a comparison between patients with or without any given cardiac disease condition, renin was significantly elevated in patients with either hypertension (36.4% vs 15.9%), CAD (33.9% vs 22.1%), or impaired LVEF (47.3% vs 24.8%). The angiotensin-renin ratio was elevated in AF patients and in patients with hypertensive cardiomyopathy. Patients with AF and coexisting hypertension had elevated renin more frequently than AF patients without coexisting hypertension (35.3% vs 16.5%; P   =  .005). Patients with persistent/permanent AF more frequently had elevated renin than patients with paroxysmal AF (34.1% vs 15.8%; P   =  .007). This prospective study of consecutive cardiac disease patients referred for cardiac catheterization has revealed distinct cardiac disease condition-associated differences in the frequencies of elevations in plasma renin, PAC, and the aldosterone-renin ratio.